72 Aspects of leadership best learnt at medical school and how these relate to australian medical council graduate outcomes. (12th November 2018) - Lyons, Oscar; McHardy, Karina; Bagg, Warwick; Wilkinson, Tim
Abstract : Introduction/background: Leadership is a core competency of doctors. However, specific learning outcomes for leadership are not well defined in medical school curricula in New Zealand and Australia. Aim: Define learning outcomes (LOs) for leadership in pre–qualification medical curricula Evaluate the extent to which Australian Medical Council (AMC) standards meet LOs for medical leadership Methods: After conducting a literature search the UK's Medical Leadership Competency Framework (MLCF) was selected as the 'gold standard' framework. Each author assessed whether relevant AMC standards sufficiently aligned to each MLCF domain, and consensus was achieved. Results: No clear 1:1 relationship between AMC and MLCF LOs. Many standards were too general or too specific. Significant interpretation of LO intent was required. Many existing AMC outcomes fit within the leadership framework. These could be more explicit. Some key elements of leadership are not yet encapsulated by AMC LOs (e.g. tools for system improvement/audit). Many MLCF competencies could be introduced into medical school curricula as foundations for further development after graduation. Some MLCF competencies are more effectively learnt after graduation. Conclusions: Leadership is multidimensional. Some dimensions may be more appropriately learnt after medical school. There are however significant gaps in current curricula as defined by the AMC, which could be met more effectively using the MLCF guidance. Discussion: MLCF leadership domains are not yet sufficiently aligned to current AMC standards. This suggests further work is required to ensure medical curricula meet the leadership needs of our graduates.